2016
DOI: 10.3390/ijms17050745
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Copper(II) Complexes, Loaded or Unloaded into a Nanostructured Lipid System, against Mycobacterium tuberculosis

Abstract: Tuberculosis (TB) is an infectious disease caused mainly by the bacillus Mycobacterium tuberculosis (Mtb), presenting 9.5 million new cases and 1.5 million deaths in 2014. The aim of this study was to evaluate a nanostructured lipid system (NLS) composed of 10% phase oil (cholesterol), 10% surfactant (soy phosphatidylcholine, sodium oleate), and Eumulgin® HRE 40 ([castor oil polyoxyl-40-hydrogenated] in a proportion of 3:6:8), and an 80% aqueous phase (phosphate buffer pH = 7.4) as a tactic to enhance the in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Silva et al15,17 performed cytotoxicity assays (IC 50 ) of complexes 1, 2, and 3 using Vero (ATCC ® CCL-81), J774A.1 (ATCC ® TIB-67), and MRC-5 (ATCC ® CCL-171) cell lines. No toxic effects of the complexes were identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silva et al15,17 performed cytotoxicity assays (IC 50 ) of complexes 1, 2, and 3 using Vero (ATCC ® CCL-81), J774A.1 (ATCC ® TIB-67), and MRC-5 (ATCC ® CCL-171) cell lines. No toxic effects of the complexes were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of the antimicrobial activity showed the activity and selectivity of the copper(II) complexes against bacteria, such as Staphylococcus aureus and Escherichia coli , were increased after the incorporation of the complexes into these systems, by analysis of cellular viability 15. Another study conducted by the same group showed that the copper(II) complexes loaded into nanostructured lipid systems also exhibited increased activity against M. tuberculosis 17. Therefore, research into nanostructured systems has intensified in order to improve the solubility of copper(II) complexes and achieve controlled release 18…”
Section: Introductionmentioning
confidence: 99%
“…The lower the PDI, the greater the uniformity of the particles (Goyal et al, 2012). For the zeta potential, the negative charge obtained comes from the components of the formulations, such as cholesterol, which in its structure has a free hydroxyl group [OH −] − and soy phosphatidylcholine, which has free ester groups [−OC = O −] − (Silva et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…(Figure 34). The nano-sized drug delivery systems increased their antimycobacterial activity, decreased cytotoxicity against the Vero cell line, and consequently improved the selectivity index [122]. (Figure 34).…”
Section: Drug-based Copper Coordination Compoundsmentioning
confidence: 99%
“…Fei et al [125] reported two copper (II) complexes, compounds 119 and 120, based on dehydroabietic acid (DHA), the main component of traditional Chinese medicine rosin (Figure 35 (Figure 34). The nano-sized drug delivery systems increased their antimycobacterial activity, decreased cytotoxicity against the Vero cell line, and consequently improved the selectivity index [122]. A recent study on the cyto-genotoxicity of Cu(II) compounds 116-118 with INH was conducted by Fregonezi et al and also concluding that the compounds show no cytotoxicity in therapeutic doses [123].…”
Section: Natural Product-based Copper Coordination Compoundsmentioning
confidence: 99%